Penggunaan Payment Gateway “Go-Pay” Dan Kinerja UMKM: Studi Pada Coffee Shop Di Kota Salatiga The Use Of Payment Gateway "Go-Pay" And Msmes Performance: Study On Coffee Shop In Salatiga City - Raynaldi Pangestu; Maria Rio Rita (EBBANK, 2022)
Fintech is the result of a combination of financial services and technology that results in a business model from conventional to modern. There are several types, including Payment Gateways, Peer to Peer Lending, Risk and Investment Management, Market Aggregators, Clearing and Settlements. One of the fintechs that is currently developing and widely used is the Go-Pay feature in the Go-Jek application. The indicator that is used to measure the financial performance of Payment Gateway (Go-Pay) is sales revenue and the profit increase which affect of MSMEs using Go-Pay, while the measure of non-financial performance is the increase in the number of customers and the growth of the company. This research was conducted to examine the effect of using Go-Pay in improving the financial and non-financial performance of MSMEs, namely the Coffee Shop in the city of Salatiga. Data collection techniques using 42 respondents. By using the analysis technique of normality test, validity, reliability, coefficient of determination, and t test. The results of the t test and the coefficient of determination show that the use of the Go-Pay payment gateway as a substitute for cash payment at the coffee shop in Salatiga City can improve the company's financial performance but has no effect on the non-financial performance of the company.